A novel study of tungsten oxide nanocrystallites as fuel additive for diesel oil. Issue 1 (1st January 2021) - Jamil, Akmal
Abstract : In this paper, a basic solvothermal synthesis using sodium tungstate as a precursor is reported to prepare tungsten oxide (WO3 ) particles. XRD data confirmed the highly crystalline nature. The broad peaks of XRD patterns estimated the nanocrystallites of WO3 . The average crystallite size as was 95 nm. Scanning electron microscopy showed the morphologically cube-like particles with aggregation that was converted to larger brick-like particle of WO3 after calcination. WO3 was used as fuel additive in diesel oil. Fire and flash points of diesel oil were enhanced to 49°C and 54°C respectively. The calorific value was increased up to 36580 Jg −1 . Thus fuel efficiency was enhanced by use of WO3 as an additive. The use of different concentrations of WO3 (20, 40, 60, 80 ppm) as fuel additive has been also explored in this paper. The observed additive properties of WO3 suggested the potential applications of such metal oxides.